Molecular Epidemiology of Influenza Virus Using RT-PCR and its Association with ABO Blood Group System and Age-Related Susceptibility - Jihad, Noor A. (American Journal of Biology and Natural Sciences, 2026)
Influenza is a constant, heavy burden on medical facilities, with millions of severe cases and an incredible amount of death each year. Precise diagnosis is critical for the management of epidemics and reverse transcription PCR (RT-PCR) became preferred approach due to its capability to accurately recognize the virus even in low concentrations in clinical specimens. Objectives: The current research sought to assess the validity of RT-PCR targeting conserved matrix (M) gene in detecting influenza and to assess if patient age cohort or ABO blood type impacts the probability of testing positive. Methods: One hundred patients with influenza-like illness (ILI) were screened with nasopharyngeal swabs. Viral RNA was identified in all samples by RT-PCR with a M gene target. The participants were divided into four age groups (<10, 10–20, 21–40, and >40 years) and by ABO blood groups; substantial variations between groups were determined by the Chi-square test. Result: Influenza type A positive samples were 35 % (35/100). The youngest children, under 10 years old, had the highest rate of 41%. The 10–20 year old group exhibited the second highest positivity rate at 29%, followed by the over 40s at 18%, and the 21–40 year olds at 12%. In terms of blood groups, type A had the elevated number of confirmed cases (34%) preceded by O (29%), B (23%) and AB (14%). Statistical testing revealed no significant association among influenza positivity and age group (χ² = 1.85, p = 0.60) or blood type (χ² = 0.72, p = 0.87). Conclusions: RT-PCR is a robust, sensitive tool for the recognition of influenza A in medical practice and surveillance settings. Younger children were more likely to get infected, although this wasn't statistically meaningful, possibly owing to the small size of the research. In this cohort, blood type had no substantial impact on susceptibility to influenza.